Intertemporal stability of uncertainty preferences - Dürsch, Peter; Römer, Daniel; Roth, Benjamin (Journal of economic psychology, 2017)
We analyze the stability of ambiguity preferences experimentally, by repeatedly eliciting ambiguity attitudes towards multiple 3-color Ellsberg urns over a period of two months. 57% of the choices show stable preferences over this time period. This is signiﬁcantly higher than random choices would suggest, but signiﬁcantly lower than the level of consistency when measures are taken back-to-back (75%). Over the same time frame, we do not ﬁnd a signiﬁcant change in the consistency of risk preferences. For subjects who are able to recall their ambiguity decision after two months correctly, the share of consistent choices does not drop signiﬁcantly over time.